Control Allocation Approach Using Differential Steering to Compensate for Steering Actuator Failure - Alexander Seiffer; Michael Frey; Frank Gauterin (IEEE Open Journal of Intelligent Transportation Systems)
Wheel-selective drives on the steered axle of a vehicle with Ackermann steering allow for the generation of steering torque without the use of a steering actuator. If different drive torques are applied to the left and right driven wheels, their effect on the steering torque is not balanced, and a resulting steering torque remains (differential steering). Thus, the function of a steering actuator can be replaced, e.g., in case of a failure. Previous studies have demonstrated the effectiveness of controlling a vehicle using differential steering. However, the vehicle dynamics during the failure-induced transition from actuator-based to differential steering control have not been thoroughly investigated. In this work, we utilize a cascaded vehicle dynamics control approach with control allocation to distribute the total drive and steering torques to the available actuators in an overactuated chassis system. Based on both simulation studies and validation experiments with a demonstrator vehicle, we investigate the vehicle dynamics immediately following actuator failures. Our cascaded approach ensures precise vehicle guidance in both nominal and redundancy mode via differential steering. After a sudden actuator failure, vehicle guidance is reliably maintained, even in dynamic driving conditions, as the approach also considers the effect of drive torque distribution on the total yaw torque (torque vectoring). The analyses conducted using the proposed approach demonstrate that a safe transition to cross-actuator functional redundancy after an actuator failure is achievable. Consequently, differential steering can be evaluated as a suitable basis for cross-actuator functional redundancy concepts to enable fault-tolerant operation of steer-by-wire systems.